Reactive slow waves in sleep underlying several physiological and pathological NREM conditions.Comments on Flamand, et al . Sleep 2018;41(10). doi:10.1093/sleep/zsy139 - Péter Halász; Liborio Parrino; Anna Szűcs (Sleep, 2019)
STUDY OBJECTIVES: Obstructive sleep apnea (OSA) is associated with structural, microstructural, functional, vascular, and metabolic brain alterations. Continuous positive airway pressure (CPAP) is the first-line treatment for OSA, but whether OSA-related abnormalities on brain magnetic resonance imaging (MRI) improve after treatment remains uncertain. This systematic review synthesized longitudinal MRI evidence on brain changes following CPAP therapy in adults with OSA. METHODS: PubMed/MEDLINE, Scopus, and Web of Science were searched from database inception to December 2025. Eligible studies included adults with OSA who underwent brain MRI before and after CPAP therapy or were compared with untreated, sham-treated, best-supportive-care, or healthy control groups. MRI outcomes included structural, diffusion, functional, perfusion, cerebrovascular reactivity, magnetic resonance spectroscopy, susceptibility-related, and perivascular-space measures. Risk of bias was assessed using an adapted Newcastle-Ottawa Scale. Findings were synthesized qualitatively because of substantial heterogeneity. RESULTS: Thirty studies were included. Reported post-CPAP MRI changes were heterogeneous and included gray matter or cortical alterations, white matter microstructural changes, modified functional connectivity and regional activity, perfusion or cerebrovascular reactivity changes, and preliminary metabolic, susceptibility-related, and perivascular-space findings. Results varied across MRI techniques, anatomical targets, CPAP duration, adherence definitions, comparator groups, and analytical methods. CONCLUSIONS: The available longitudinal MRI literature suggests possible domain-specific brain changes after CPAP, but the evidence is largely exploratory because most studies were small and nonrandomized and used heterogeneous imaging and analytical approaches. The findings do not establish reproducible MRI treatment effects or support routine MRI monitoring of individual response. Larger, prospectively specified, harmonized longitudinal studies are needed.